Aggregate shocks, poor households and children - Mendoza, Ronald U (Archīum Ateneo, 2009)
The global financial crisis that erupted in 2008, coupled with food and fuel price volatility, are likely to affect developing countries and within them the vast majority of the world’s poor population in profound ways. This paper maps the different channels through which their effects could be transmitted to the developing world and illustrates a basic framework of shock transmission to a developing country from the macro- to the micro-levels, also considering possible adverse feedback effects. Aggregate shocks are going to be an increasingly common feature of the global economic landscape, and these shocks could result in poverty traps, generating effects that harm not just present, but also succeeding generations. Social budgeting and social protection will be critical in order to preserve investments in children and human development and shield poor households and vulnerable children and women from the worst effects of these shocks.